Experimental research with pseudo-words, a review of phonosymboliques correlations: français (Signifiances (Signifying), 2019)
Recently, scientific community has observed a renewed interest in research on sound symbolism. Despite this considerable growth, the content of this studies, mainly in English, is still relatively unknown by French community. This article will present some of these studies: the experimental studies carried out with pseudo-words to present acquired knowledge. Thus, we will establish a list of sound-symbolic correlations attested by this literature, that is, a list of the motivated relations that exist between some phono-articulatory features and some semantic features.